Peran Pendidikan Sebagai Agen Perubahan Sosial di RT 33 Singa Gembara Sangatta Utara - Yusuf, Muhammad; Rizki, Muhammad; Yasin, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This study examines the role of pendidikan as an agent of social change in RT 33 Singa Gembara, Sangatta Utara, which faces challenges such as kemiskinan struktural, low educational participation, and environmental degradation due to mining activities. The research questions focus on: the role of pendidikan formal, nonformal, and informal as agents of social change; the main challenges faced by education in promoting socio-economic and environmental transformation; and community-based educational strategies to overcome structural poverty and social conflict. The study aims to identify the contributions of various forms of education to community transformation comprehensively. The method used is a qualitative descriptive approach with data collected through in-depth interviews, observations, and documentation involving five key informants representing formal, nonformal, and informal education perspectives. The results show a synergy between formal education (elementary and SMP Bina Adab Nusantara), nonformal education (PKK program), and informal education (mosque recitations), which has improved basic literacy, economic independence, and social tolerance, despite obstacles such as family economic priorities, pollution, and limited facilities. Community-based strategies such as digital literacy, mutual cooperation forums, and A/B/C package tutoring were effective in reducing poverty and social conflict. This research confirms education as a driver of sustainable social transformation and recommends collaboration among the government, educational institutions, and communities to strengthen its impact